IMPLEMENTASI PERBUP NO 2 TAHUN 2018 TENTANG TRANSAKSI NON TUNAI PADA PROGRAM E-RETRIBUSI DI PASAR BLAMBANGAN KABUPATEN BANYUWANGI - Adam Achbar Rafsanzani; Niko Pahlevi Hentika; Dimas Imaniar (JURNAL KATARSIS, 2026)
The fundamental problem addressed in this study is the persistent leakage of locally-generated revenue from market retribution due to opaque manual cash payment systems in Banyuwangi Regency. The research aims to describe and analyse the implementation of Banyuwangi Regent Regulation Number 2 of 2018 concerning Non-Cash Transactions on the E-Retribution programme at Blambangan Market, utilising the dimensions of communication, resources, disposition, and bureaucratic structure. The methodology employed a descriptive qualitative approach through in-depth interviews with informants selected via snowball sampling, direct field observation, and documentary study. The findings indicate that the implementation of the Electronic Market Retribution (ERPAS) programme has been relatively successful through a partnership with PT Bank Jatim. Policy communication was conducted through two-way socialisation, human resources were equipped with Standard Operating Procedures, although supporting facilities such as Electronic Data Capture (EDC) machines were still prone to technical disruptions. The implementers’ disposition demonstrated high commitment, yet resistance from some traders due to the requirement of upfront deposit was still encountered. The bureaucratic structure exhibited clear task division and routine supervision. The conclusion underscores that the success of this policy implementation is determined by the synergy of the four dimensions and the capacity to address technical constraints and traders’ digital literacy. The study contributes recommendations for strengthening infrastructure capacity and continuous socialisation for the replication of similar policies.